Effects of Aspirin Therapy on Bypass Efficacy and Survival of Patients Receiving Direct Cerebral Revascularization - Xiang, Yanxiao; Zhang, Ping; Zhao, Peng; Sun, Tao; Wang, Fei; He, Yiming; Wang, Donghai; Liu, Anchang (Frontiers in Pharmacology, 2022)
Background: Both patency maintenance and neoangiogenesis contribute to cerebrovascular bypass efficacy. However, the combined impact of the above two indicators on postoperative revascularization following superficial temporal artery to middle cerebral artery (STA- MCA) bypass have been less well elucidated. Meanwhile, reports of postoperative aspirin therapy still present paucity of evidence with conflicting results. Objective: To investigate the correlation between STA-MCA bypass efficacy including patency, postoperative neoangiogenesis, and follow-up outcomes with comparisons between aspirin group and non-aspirin group. Methods: One hundred and eighty-one MMD patients (201 procedures) undergoing STA-MCA bypass at our institution (2017-2019) were retrospectively reviewed. Bypass efficacy level, postoperative complications were collected and statistical correlations performed.Trial registration: Chinese Clinical Trial Registry, ChiCTR2100046178. Results: Among 95 PS-matched pairs, aspirin group presented a significantly more favorable bypass efficacy than non-aspirin group [odd ratio (OR) 2.23, 95% confidence interval (CI) 1.11-4.61; P= 0.026]. Multivariate logistic regression analysis confirmed the profound impact of aspirin as the independent predictor of bypass efficacy [adjusted OR 2.91, 95% CI 1.34-6.68; P= 0.009]. Remarkable negative correlation was found between bypass efficacy and the rate of ischemic complications (Phi=-0.521). Postoperative aspirin therapy was associated with a non-significant trend towards lower incidence of ischemic events [OR 0.73, 95% CI 0.23-2.19; P= 0.580]. No significant difference in bleeding rates was observed between aspirin and control group [OR 1.00, 95% CI 0.12-8.48; P= 1.000]. Conclusion: In patients undergoing STA- MCA bypass procedures, bypass efficacy is a good predictor of follow-up outcomes. Postoperative aspirin therapy can improve patency, neoangiogenesis and overall bypass efficacy and thereby protect against postoperative ischemic complications.